2001
DOI: 10.1242/dev.128.17.3269
|View full text |Cite
|
Sign up to set email alerts
|

Thelin-11LIM homeobox gene specifies olfactory and chemosensory neuron fates inC. elegans

Abstract: Chemosensory neuron diversity in C. elegans arises from the action of transcription factors that specify different aspects of sensory neuron fate. In the AWB and AWA olfactory neurons, the LIM homeobox gene lim-4 and the nuclear hormone receptor gene odr-7 are required to confer AWB and AWA-specific characteristics respectively, and to repress an AWC olfactory neuron-like default fate. Here, we show that AWA neuron fate is also regulated by a member of the LIM homeobox gene family, lin-11. lin-11 regulates AWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…4G), which arise from the same parental cell in the last round of C. elegans embryonic cell divisions. Their differentiation has previously been used as a model for the study of the regulation of cell fate decisions (40). In our data, 136 genes were differentially expressed between these two cell types (fold difference > 3, false discovery rate < 5%; Fig.…”
Section: Neuronal Cell Typesmentioning
confidence: 71%
“…4G), which arise from the same parental cell in the last round of C. elegans embryonic cell divisions. Their differentiation has previously been used as a model for the study of the regulation of cell fate decisions (40). In our data, 136 genes were differentially expressed between these two cell types (fold difference > 3, false discovery rate < 5%; Fig.…”
Section: Neuronal Cell Typesmentioning
confidence: 71%
“…Several previous studies have suggested that AWC is also a default identity state for several other amphid sensory neuron classes, as this ground state is revealed upon removal of the terminal selector gene of the respective amphid sensory identity. Specifically, loss of AWA identity in odr-7 or lin-11 mutants, loss of ASG identity in unc-130; odr-7 double mutants, or loss of AFD identity in ttx-1 mutants has been proposed to reveal an AWC ground state (Sagasti et al, 1999;Sarafi-Reinach & Sengupta, 2000;Sarafi-Reinach et al, 2001;Satterlee et al, 2001;Lanjuin et al, 2003). However, these conclusions were mainly if not exclusively based on the ectopic expression of the GPCR str-2, an AWC ON marker.…”
Section: Distinct Differentiation Mechanisms For Distinct Olfactory N...mentioning
confidence: 99%
“…LIM-homeodomain regulatory genes are expressed as progenitor cells exit the cell cycle and generate different neuron cell types in a spatiotemporal pattern. They are involved in developing thermosensory, olfactory, chemosensory, and mechanosensory neurons (Cassata et al, 2000;Sarafi-Reinach et al, 2001;Srivastava et al, 2010).…”
Section: Discussionmentioning
confidence: 99%